2019
DOI: 10.31254/phyto.2019.8209
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostical and Phytochemical Evaluation of Gandhakadi Yoga

Abstract: Thalassemia is one of the most challenging form of Haematological disorders. Gandhakadi Yoga is an Ayurvedic medicine comprising of SHUDDHA GANDHAKA (Sulphur), VIDANGA (Embelia ribes Burm.f.), AGASTYA PATRA (Sesbaniya grandifoliya Linn.), SHIGRU PATRA (Moringa Oleifera Lam.). Gandhakadi Yoga is a customized preparation of the formulation proposed for Loha Sevanajanya Vikara Prashamana (iron overloading) in Ayurveda Prakasha. here in Gandhaka and Vidanga are triturated with Agatsya patra Swarasa and then used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Mooradian (1993) reported that steroid compounds are an index of antioxidant properties of these compounds. (Selvin & Lipton, 2004;Fayaz et al, 2005;Somepalli et al, 2007;Adaikalaraj et al, 2011).…”
Section: Phytochemical Resultsmentioning
confidence: 99%
“…Mooradian (1993) reported that steroid compounds are an index of antioxidant properties of these compounds. (Selvin & Lipton, 2004;Fayaz et al, 2005;Somepalli et al, 2007;Adaikalaraj et al, 2011).…”
Section: Phytochemical Resultsmentioning
confidence: 99%
“…Aqueous extracts of Gracilaria corticata reported the highest amount of alkaloids compared with other seaweed extracts and alkaloids were absent in Ulva fasciata. Many reports revealed the presence of alkaloids in seaweeds and some of seaweed species have been investigated for their biological activities as well (Adikalaraj et al, 2011). Alkaloids are commonly found to have antimicrobial properties (Wangchuk et al, 2016) against both gram-positive and gram-negative bacteria (Lavanya and Veerappan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the phytochemical investigation of seaweeds revealed the presence of various secondary metabolites in a varied degree. Recently, many studies have been conducted on the phytochemistry of seaweeds worldwide (Selvin and Lipton, 2004;Fayaz et al, 2005, Somepalli et al, 2007Adikalaraj et al, 2011). It suggests that seaweeds have a great medicinal value and have been extensively used in the pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 99%